Antiinflammatory and antioxidant activity of plants used in traditional medicine in Ecuador - De Las Heras B.; Slowing, K.; Benedí J.; Carretero, E.; Ortega, T.; Toledo, C.; Slowing, K.
Ethanolic extracts from 15 plant species, representing eight different families, used in traditional medicine in Ecuador were evaluated for antiinflammatory and antioxidant activities. Conyza floribunda, Eupatorium articulatum, Bonafousia longituba, Bonafousia sananho, Tagetes pusilla and Piper lenticellosum extracts showed a significant antiinflammatory activity in vivo in the carrageenan-induced paw oedema model in mice. The extracts were also tested in vitro for their ability to inhibit lipid peroxidation and to scavenge superoxide and hydroxyl radicals. E. articulatum extract possesses both activities. Baccharis triner6is, E. articulatum and Phytolacca ri6inoides extracts were active as antioxidants
Keywords: ANTIINFLAMMATORY ACTIVITY; RADICAL SCAVENGER; LIPID PEROXIDATION; TRADITIONAL MEDICINE; ECUADORIAN PLANTS